Pengaruh Customer Relationship Management, Kepuasan Pelanggan, dan Kualitas Pelayanan terhadap Loyalitas Pelanggan di Toko Riska - Mulisa Mulisa; Tomy Dwi Cahyono; Willia Ismiyarti; Erwin Mardinata (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the influence of Customer Relationship Management (CRM), customer satisfaction, and service quality on customer loyalty at Toko Riska, a retail business located in Batu Alang Village. Toko Riska sells various women's products, including clothing, hijabs, bags, beauty products, and accessories. This study uses a quantitative approach with a survey design. Given the population is not precisely known (infinite population), the proportion formula at a 95% confidence level and a 10% margin of error resulted in a minimum sample size of 96 respondents, which was rounded up to 100 respondents, and selected through a purposive sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS. The t-test results show that CRM has a positive and significant influence on customer loyalty (β = 0.312; t = 3.847; sig. = 0.000), customer satisfaction has a positive and significant influence (β = 0.284; t = 3.521; sig. = 0.001), and service quality has a positive and significant influence (β = 0.341; t = 4.193; sig. = 0.000). The F-test yielded an F-value of 42.315 (sig. = 0.000), which confirmed the significance of the simultaneous. The coefficient of determination (R²) of 0.568 indicates that 56.8% of the variation in customer loyalty is explained by the three independent variables. This study recommends that Toko Riska strengthen CRM practices, increase customer satisfaction, and improve service quality to encourage long-term customer loyalty.